Rural-urban linkages: Masvingo's doublerooted female heads of households - Muzvidziwa, Victor N. (University of Zimbabwe Publications, 2016)
This article results from research on female heads of households in a small Zimbabwean city. Urban-rural linkages constituted an important, on-going survival strategy for women in the research sample. Despite my respondents' desire to stay and to source a living in town, most maintained rural linkages in order to cope with various problems in town. Without a foot in the rural area, most women would not have been able to pursue their desired objective of being permanently urban. Although the women were urban-oriented, they used kin networks in ways that maximised their chances of surviving in town, against the structural constraints imposed by central and local-level bureaucracies. The article explores ways in which the women pursued the strategy.